Optical imaging of flavor order in flat band graphene - Tian Xie; Tobias M. Wolf; Siyuan Xu; Zhiyuan Cui; Richen Xiong; Yunbo Ou; Patrick Hays; Ludwig F. Holleis; Yi Guo; Owen I. Sheekey; Caitlin Patterson; Trevor Arp; et al. (Nature Communications)
Abstract Spin- and valley flavor polarization plays a central role in the many-body physics of flat band graphene, with Fermi surface reconstruction — often accompanied by quantized anomalous Hall and superconducting state — observed in a variety of experimental systems. Here we describe an optical technique that sensitively and selectively detects flavor textures via the exciton response of a proximal transition metal dichalcogenide layer. Through a systematic study of rhombohedral and rotationally faulted graphene bilayers and trilayers, we show that when the semiconducting dichalcogenide is in direct contact with the graphene, the exciton response is most sensitive to the large momentum rearrangement of the Fermi surface, providing information that is distinct from and complementary to electrical compressibility measurements. The wide-field imaging capability of optical probes allows us to obtain spatial maps of flavor order with high throughput, and with broad temperature and device compatibility. Our work helps pave the way for optical probing and imaging of flavor orders in flat band graphene systems.